Dynamic simulation and experimental performance of an adsorbed natural gas system under variable charging conditions - Mirzaei, S.; Shahsavand, A.; Ahmadpour, A.; Garmroodi Asil, A.; Arami-Niya, Arash (2022)
Adsorbed natural gas (ANG) technology is considered a cost-effective and sustainable energy storage system that can offer a leading clean and environmentally friendly combustion fuel. Despite the benefits of ANG systems, still, there are some challenges in simulation of these systems accurately under actual conditions. The actual charging condition of ANG vessel with variable gas flow rate was simulated and experimentally validated for the first time. For this purpose, we proposed a new time-dependent equation to monitor methane's variable injection flow rate into the vessel. Dynamic methane storage was experimentally tested to validate the simulation results using a custom-built pressurised ANG vessel (∼300 cm3) filled with various in-house prepared adsorbents (i.e. AC1 and AC2) under the loading condition of 40 bar and 298 K. Also, the thermal behaviour of the ANG vessel was studied via experimental observations. A 2D distributed dynamic model, solved by COMSOL Multiphysics software, was developed to assist the simulation in predicting pressure and temperature variations inside the ANG bed. Analysis of the ANG vessel's performance exhibited higher thermal fluctuations attributed to the adsorbent with superior isothermal methane storage capacity. Due to the low thermal conductivity of both adsorbents, a significant temperature rise was observed in the central region of the bed. Sensitivity analysis shows that increasing the length and diameter of the ANG tank leads to a longer required time for charging the tank up to the desired pressure and relative decreases in the temperature profile. Moreover, increasing heat capacity of adsorbent from 800 to 1350 J/kg.K caused 37% reduction in the temperature variations and 7.7% enhancement in gravimetric methane storage efficiency.